2007
DOI: 10.1177/1744259107073221
|View full text |Cite
|
Sign up to set email alerts
|

Previous Experimental Studies and Field Measurements on Moisture Buffering by Indoor Surface Materials

Abstract: An increased interest in moisture buffering in the indoor environment and the development of more refined hygrothermal calculation tools call for a better understanding of the phenomenon. There are many materials indoors with potential to act as moisture buffers, ranging from traditional finishing materials as gypsum plaster to textiles. The objective of this study is to show that the interest in moisture buffering is not a new issue. There have been significant laboratory studies made in the past. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 7 publications
(6 reference statements)
0
16
0
Order By: Relevance
“…Such method corresponds to a high relative humidity (RH) cycle for a set time span characterising the adsorption followed by a low humidity cycle to characterise desorption, the mass change of the sample being monitored during the process. This type of experiment was then continued by several authors as reported by (Svennberg et al, 2007). A Japanese Industrial Standard (JIS) (JIS, A 1470(JIS, A -1, 2002 test was developed using the same principals and the outcome of the Nordtest project also proposed the same type of testing for moisture buffering evaluation (Rode et al, 2005, Roels andJanssen, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Such method corresponds to a high relative humidity (RH) cycle for a set time span characterising the adsorption followed by a low humidity cycle to characterise desorption, the mass change of the sample being monitored during the process. This type of experiment was then continued by several authors as reported by (Svennberg et al, 2007). A Japanese Industrial Standard (JIS) (JIS, A 1470(JIS, A -1, 2002 test was developed using the same principals and the outcome of the Nordtest project also proposed the same type of testing for moisture buffering evaluation (Rode et al, 2005, Roels andJanssen, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Typical results for plasters (lime plaster, lime cement plaster and cement plaster) from the work undertaken in Germany varied between 35 and 55 g/m 2 after 8 h. The 'absorption coefficients' were the strongest for natural fibre carpets with 30-36 g/m 2 √h. Similar experiments were conducted at Lund University on the typical building and furnishing materials used in Scandinavian houses between 1980 and 2000 (Svennberg et al, 2007).…”
Section: Step-response Test Protocolsmentioning
confidence: 96%
“…The step-response method was first used at the Fraunhofer Institute for Building Physics in Germany (Fraunhofer IBP) and at Lund University in Sweden. A review was written by Svennberg et al (2007) on experiments undertaken between 1960 and 2000 which included five papers. In Germany, the tested materials included wall materials, wood, carpets and curtains.…”
Section: Step-response Test Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory results obtained over 40 years for indoor finishing were presented in Ref. [39]. A lightweight building envelope wall exposed to real atmospheric conditions is reported in Ref.…”
Section: Introductionmentioning
confidence: 98%